Negotiating autonomy: The linkages between intimate partner violence, women's paid work status and birth outcomes - Subhasree Ghatak; Meghna Dutta (Administrative Sciences, 2023)
Maternal and child health is severely impacted by adverse birth outcomes leading to a public health concern. A whole host of socioeconomic factors are instrumental in determining birth outcomes. Importantly, there is an intricate relationship between women's autonomy, the perpetration of intimate partner violence in households, women's paid work status and their consequent impact on birth outcomes. Noting this, we ask how intimate partner violence and women's work status interact and how women's 'autonomy' is negotiated to mitigate adverse birth outcomes such as miscarriage, abortion, stillbirth, low birth weight and preterm birth. We use the nationally representative NFHS-5 data for India and use multiple correspondence analyses to create an index of women's autonomy, and multinomial logistic regression has been used to determine the relation. Women's working status in association with the perpetration of intimate partner violence contributes significantly to adverse birth outcomes. The study found that mitigation of adverse birth outcomes, which is necessary for bringing about improvements in maternal and child health, is contingent on a multiplicity of social factors, which requires redressal in association to ensure a reduction in adverse birth outcomes.
Keywords: 350; adverse birth outcomes; India; intimate partner violence; maternal health; women's autonomy